Utilization of excess microorganisms as carbon and electron sources in the sulfate reduction process - Yilmaz, Tülay; Uçar, Deniz (John Wiley and Sons Ltd, 2024)
BACKGROUND: The cost of the substrate plays a crucial role in sulfate-containing wastewater treatment. Utilizing a natural or low-cost substrate is essential for effective sulfate reduction. This study investigates and compares the sulfate reduction performance of excess yeast and excess activated sludge as substrates to that of ethanol, one of the most commonly used substrates. RESULTS: Both waste sludge groups underwent initial anaerobic digestion and were subsequently fed into an anaerobic up-flow bed reactor. The reactor operated through five periods using synthetic water containing 2000 mg SO42? L?1. To assess electron donor performance during transitions between carbon sources, famine periods (without substrate addition) were implemented. Maximum sulfate reduction efficiencies for ethanol, excess yeast and excess activated sludge, and yeast were 89%, 54% and 70%, respectively, with corresponding chemical oxygen demand oxidation rates of 86%, 81% and 92%. The ethanol-fed period exhibited the highest sulfide (720 mg L?1 on day 116) and alkalinity (2035 mg CaCO3 L?1 on day 109) production. It is evident that waste activated sludge, primarily composed of prokaryotic bacteria, was more susceptible to biodegradation than eukaryotic waste yeast. CONCLUSIONS: While ethanol is a favorable source of electrons, this study suggests that the waste products of biological processes can serve as an alternative to ethanol for sulfate reduction. This approach has the potential to reduce operating costs in treatment systems by using biological waste as a carbon source. © 2023 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI). © 2023 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).
Keywords: acid mine drainage remediation; biological sludge stabilization; sulfate pollution treatment; sulfidogenic process